THE EUROPEAN UNION REFERENDUM CAMPAIGN: IDEOLOGIES AND MANIPULATIVE FEATURES IN THE BRITISH PRESS DISCOURSE - Doukha, Fatima; Mansouri, Brahim (PEOPLE: International Journal of Social Sciences, 2021)
Undeniably, Media plays a pivotal role in every aspect of peoples’ daily lives and significantly during times of great events. For decades, Media generally and the press particularly have been harnessed by politicians and commentators to impart their messages to the general public to either control or legitimize their political attitudes and goals. The rise of online news and the systematic decline of newspaper circulation did not herald the end of the significance of the press to political debate. People’s actions and opinions are deeply amenable and manipulated by the hidden ideologies adopted by the online press and embedded within the news texts. During the referendum campaign of 2016, the press was a primary source of political information and had a significant position in setting the agenda for the mainstream Media (Levy et al., 2016). This paper examines critically the way the online press has manipulated people’s views in the referendum campaign of 2016 on the United Kingdom’s membership in the European Union. It focuses mainly on the micro-level of study to unveil the implicit ideologies which the newspaper discourse is laden with. Norman Fairclough’s model of CDA is the appropriate approach for this study that is to analyze the linguistic characteristics of vocabulary and grammar which reflect power relations and the ideological persuasion in discourse (Fairclough, 2001, p.91). The result reveals the use of experiential, expressive, and relational values by both campaigners meant to influence and direct the individual’s vote on the day of the referendum.